The Role of Educational Psychology in Enhancing the Qualityof the Teaching and Learning Process - Hilalludin Hilalludin; Dedi Sugari; Shada Al-Nomani; Muzanni Muzanni (Ar-Ruhul Ilmi: Jurnal Pendidikan dan Pemikiran Islam, 2025)
The quality of learning in Indonesia continues to face various challenges, including the diversity of student characteristics, learning motivation, and the effectiveness of teaching strategies. Educational psychology plays a crucial role in understanding and responding to these complexities by providing a scientific foundation for teachers in managing the learning process. This literature research aims to analyze the role of educational psychology in improving the quality of teaching and learning processes. Using a qualitative approach, data were collected from various academic sources such as books, journal articles, and previous studies. The results of the study reveal that educational psychology helps teachers in six key areas: understanding individual differences, enhancing learning motivation, designing effective learning strategies, improving teacher-student interaction, managing classrooms more constructively, and applying more objective and reflective learning evaluations. These findings indicate that educational psychology not only enhances the effectiveness of learning but also encourages the creation of an inclusive and student-centered learning environment. This study contributes conceptually to educators and institutions to strengthen their pedagogical foundation through psychological understanding that is humanistic and responsive to student needs.